Apelação no código de processo civil: uma análise sob o prisma do princípio da efetividade - Chaves, Giovanni Weine Paulino (2013)
The present dissertation, elaborated is based on the deductive method, through the use of the General Theory of Resources concepts, by the main types of judgments existing in the Code of Civil Procedure, the interlocutory judgment and sentence, as well as the features and effects that challenge these decisions, we sought to identify on this theme one of the greatest evils facing the justice system in the world, which is the processing delays. This slowness in adjudication affects seriously the principle of effectiveness, one of the postulates of procedural law and society as a whole. Thus, the use of tort serves to fight the interlocutory decision and appeal which challenges the judge`s ruling. It is a resource for excellence in appellate system as it meets with the most awaited decision of the process. In weighing the importance of the appeal that seeks to oppose the court decision today by the numerous reforms that the procedural system has been through, it has ended up to transform the process ineffective or inconsistent, for it is much easier to have efficacy in a interlocutory decision for preliminary injunction than by judgment on the merits of the judge. This is due to the prevision of the resources and their effect to those decisions. That is, the interlocutory decision involves interlocutory appeal only in the devolved effect, allowing its provisional execution, and the sentence has as recourse to appeal the double effect, remanding and suspension, which necessarily prevents its provisional execution. But it undeniably shows a paradox, because as to give effect to a measure that is based on a mere probability by a summary cognition, partial and superficial, and stop it on a decision by a court that is closer to the truth and sure, for a full and depleting cognition? It is seriously affect the principle of effectiveness. Therefore, starting from this ineffectiveness, sought to defend the solution of this problem with the approval of the bill n. º 3.605/2004 or the new Code of Civil Procedure project that modifies the general rule the effects of appeal. That is, remanding and suspensive, as to merely remanding effect to and thereby enable the provisional execution of the judgment of the court of the first degree of jurisdiction, giving effectiveness and enhancing the decision of the magistrate, making a fair distribution of time in the process and better guaranteed principle of access to justice